Hyperspecialization and Imagenology: Perceptions and Reflections of Working and Academic Worlds - Cabezas-Cabrera, Andrés (2023)
Objective. This research aimed to analyze the student, academic, and professional perception of the hyperspecialization in imaging in Chile and its possible threat/opportunity in undergraduate training. Method. This is a qualitative approach study of an exploratory type with descriptive elements. The study subjects were ninety-five people between professionals and students. The study conducted a semi-structured interview, and established macro-categories, whose data were recorded using a textuality matrix and qualitative frequencies of own elaboration. Results. 64% of the interviewees do not know the concept of hyperspecialization in imaging, versus 36% of those who know it. However, once this concept was explained, 56% of the interviewed group was considered hyperspecialized in some area of professional performance, versus 44% who was not. Conclusion. The study found a perception of closure of the imaging discipline towards other disciplines; this discipline must be work-related to other areas of knowledge. However, the interviews revealed that the optimism and acceptance environment of the disciplinary bonding phenomenon stands out; the interviewed group perceives a better bond between the educational and working worlds.